Montažna gradnja in vidna podoba slovenskih mest in naselij - Deu, Živa (Les (Ljubljana), 2005)
General degradation of the living environment is the basic reason for the formation of new directions on the international level, which are based on different, nature and environment friendly, environment sustainable settling of the space. On the basis of sustainable development's general directions of the space, new, also detailed valuable and normative definitions for organizing settlements have been formed. The urban and architectural work in them is directed to planning accordant with given natural possibilities and inaccordance with the typically formed and identically built structures (the entire protection of building heritage). The studies and detailed analyses have shown that comprised standards of the developed-in-the-past building culture, consist of numerous valuable characteristics, which are in accordance with the principles of constant development, their consideration is also important for the preservation of the more and more important differencies between the existing diverse cultural environments. Prefabricated building, just like classical building, is a constituent part of new process in developmental forming of settlements. To attain the aim, radical changes in the architectural design of prefabricated houses will be needed, because their architecture nowadays is global, cosmopolitan and not adapted to the different natural conditions and to the existent, typically built structures in the Slovene space.
Keywords: prostorska ureditev; montažna gradnja; kulturna krajina; Slovenia; Slovenija